18+34r=-18

Combine 34 and r.

18+3r4=-18

Subtract 18 from both sides of the equation.

3r4=-18-18

Subtract 18 from -18.

3r4=-36

3r4=-36

Multiply both sides of the equation by 43.

43⋅3r4=43⋅-36

Simplify 43⋅3r4.

Cancel the common factor of 4.

Cancel the common factor.

43⋅3r4=43⋅-36

Rewrite the expression.

13⋅(3r)=43⋅-36

13⋅(3r)=43⋅-36

Cancel the common factor of 3.

Factor 3 out of 3r.

13⋅(3(r))=43⋅-36

Cancel the common factor.

13⋅(3r)=43⋅-36

Rewrite the expression.

r=43⋅-36

r=43⋅-36

r=43⋅-36

Simplify 43⋅-36.

Cancel the common factor of 3.

Factor 3 out of -36.

r=43⋅(3(-12))

Cancel the common factor.

r=43⋅(3⋅-12)

Rewrite the expression.

r=4⋅-12

r=4⋅-12

Multiply 4 by -12.

r=-48

r=-48

r=-48

Solve for r 18+3/4r=-18